The High-mobility-group domain of Sox proteins interacts with the DNA-binding domains of many transcription factors. - Wegner, Michael; et al. (Nucleic Acids Research, 2006)
Sox proteins are widely believed to team up with other transcription factors as partner proteins to perform their many essential functions during development. In this study, yeast two-hybrid screens identified transcription factors as a major group of interacting proteins for Sox8 and Sox10. Interacting transcription factors were very similar for these two group E Sox proteins and included proteins with different types of DNA-binding domains, such as homeodomain proteins, zinc finger proteins, basic helix-loop-helix and leucine zipper proteins. In all cases analyzed, the interaction involved the DNA-binding domain of the transcription factor which directly contacted the C-terminal part of the high-mobility-group (HMG) domain. In particular, the C-terminal tail region behind helix 3 of the HMG domain was shown by mutagenesis to be essential for interaction and transcription factor recruitment. The HMG domain thus not only possesses DNA-binding and DNA-bending but also protein-interacting ability which may be equally important for the architectural function of Sox proteins on their target gene promoters. © 2006 Oxford University Press.
UnivIS-Import:2015-03-09:Pub.2006.med.IB.LPCIPDBI.thehig